Chemolithoautotrophic arsenite oxidation by a thermophilic Anoxybacillus flavithermus strain TCC9-4 from a hot spring in Tengchong of Yunnan, China - Jiang, Dawei; Li, Ping; Jiang, Zhou; Dai, Xinyue; Zhang, Rui; Wang, Yanhong; Guo, Qinghai; Wang, Yanxin (Frontiers in Microbiology, 2015)
A new facultative chemolithoautotrophic arsenite-oxidizing bacterium TCC9-4 was isolated from a hot spring microbial mat in Tengchong of Yunnan, China. This strain could grow with arsenite (AsIII) as an energy source, CO2-HCO3- as a carbon source and oxygen as the electron acceptor in a minimal salts medium. Under chemolithoautotrophic conditions, more than 90 % of 100 mg/L AsIII could be oxidized by the strain TCC9-4 in 36 hours. Temperature was an important environmental factor that strongly influenced AsIII oxidation rate and AsIII oxidase (Aio) activity; highest Aio activity was found at the optimal temperature of 40 oC. Addition of 0.01 % yeast extract enhanced the growth significantly, but delayed the AsIII oxidation. On the basis of 16S rDNA phylogenetic sequence analysis, strain TCC9-4 was identified as Anoxybacillus flavithermus. To our best knowledge, this is the first report of arsenic oxidation by Anoxybacillus flavithermus. The results of this study expand our current understanding of microbially-mediated arsenic oxidation in hot spring.